Preliminary Investigation into the Cause and Cure of the Spike Disease in Sandal (Santalum album) in the North Salem Division Madras Presidency - Hart, W. C., P. E. S.; Rengaswamy, S., Rander (Indian Forester, 1926)
No abstract